A probabilistic approach for the linear behaviour of glued laminated timber. (1st October 2017) - Kandler, Georg; Füssl, Josef
Highlights: The stiffness distribution within wooden boards was modelled as random process. Stochastic perturbation method and polynomial chaos projection scheme were used. These methods returned statistical values of stiffness of glued laminated timber. Good accuracy could be observed between numerical and experimental results. Abstract: A probabilistic model for glued laminated timber (GLT) is proposed, using a random process model for the random stiffness distribution within each lamination. The random process model is derived on basis of stiffness profiles of 448 wooden Norway spruce boards obtained by non-destructive methods. Employing the Karhunen-Loève expansion, this model is used to represent the random nature of each lamination within the GLT setup. Different GLT setups are statistically analysed employing the conventional finite element framework within the so-called perturbation and polynomial chaos projection schemes. The numerical results concur well with those obtained by Monte Carlo simulation and experimentally-obtained results.